Rupture of a previously scarred uterus along with rupture bladder- an obstetric catastrophe (Journal of Dhaka National Medical College & Hospital, 2015)
Rupture uterus is a deadly obstetric emergency endangering the lives of both mother and fetus. Improved obstetric care reduces the rupture from obstructed labour but there has been increased prevalence of scar rupture, following an increase in incidence of caesarean delivery. Serious maternal bladder injury at the time of uterine rupture remains a risk of attempted vaginal birth after previous caesarean section (VBAC).Here we present a case of rupture uterus & bladder in a 29 years old 4th gravida p2+1 female presenting at East West Medical College (EWMC) hospital, Dhaka with 39 weeks pregnancy and came in shock. Successful emergency surgery and resuscitation saved her life. Ruptured uterus and ruptured bladder were found and fetus was fresh stillborn male weighing (3kg). Repair of rupture uterus and bladder was undertakenJ.Dhaka National Med. Coll. Hos. 2015; 21 (02): 61-64